Sturge Weber Syndrome (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Sturge weber syndrome is a rare sporadic condition of mesodermal phacomatosis, also called encephalotrigeminal angiomatosis (synonyms : fourth phacomatosis or mother spot), is a neurocutaneous disorder with angiomas that involve the leptomeninges (leptomeningeal angiomas) and the skin of the face (purple colored flat cutaneous haemangiomas ), typically in the ophthalmic (V1) and maxillary (V2) distributions of the trigeminal nerve. The hallmark of sturge weber syndrome is a facial cutaneous venous dilation, also referred to as a nevus flammeus or port wine stain (PWS). Because of the rarity, we report here a one & half year old male child who presented with features of the Sturge Weber Syndrome on both side of face.